2021
DOI: 10.3389/fphys.2021.625370
|View full text |Cite
|
Sign up to set email alerts
|

Current Predictive Resting Metabolic Rate Equations Are Not Sufficient to Determine Proper Resting Energy Expenditure in Olympic Young Adult National Team Athletes

Abstract: Predictive resting metabolic rate (RMR) equations are widely used to determine athletes’ resting energy expenditure (REE). However, it remains unclear whether these predictive RMR equations accurately predict REE in the athletic populations. The purpose of the study was to compare 12 prediction equations (Harris-Benedict, Mifflin, Schofield, Cunningham, Owen, Liu’s, De Lorenzo) with measured RMR in Turkish national team athletes and sedentary controls. A total of 97 participants, 49 athletes (24 females, 25 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 52 publications
0
27
1
9
Order By: Relevance
“…), as previously discussed. Balci et al (35) tested the accuracy of most used predictive equations in athletes and sedentary people, and Cunningham's equation did not present the best performance to predict the RMR on this sample. In the present study, Cunningham2 showed the best performance among all predictive equations for group and individual levels (Tables 2, 3).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…), as previously discussed. Balci et al (35) tested the accuracy of most used predictive equations in athletes and sedentary people, and Cunningham's equation did not present the best performance to predict the RMR on this sample. In the present study, Cunningham2 showed the best performance among all predictive equations for group and individual levels (Tables 2, 3).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, it was calculated the percentage of subjects that presented the estimated RMR value within ±5% and ±10% of the measured RMR. The literature proposed these thresholds as an acceptable error comparing the measured and estimated RMR (35)(36)(37). To be considered as a "good equation," all the three following criteria must be accomplished: a) no statistical difference (post hoc test, P ≥ 0.05) between measured and predicted RMR values, b) %MD ≤ ±10%, and c) %RMSE ≤ 10%.…”
Section: Discussionmentioning
confidence: 99%
“…A brief overview of relevant research shows that Cunningham 1980 equation tends to result in higher predictive values than the measured values (Balci et al, 2021; Flack et al, 2016; Staal et al, 2018; Strock et al, 2019), Cunningham 1991 closely matching the measured values (Strock et al, 2019), Harris-Benedict shows typically to be closer to the measured (Balci et al, 2021; Flack et al, 2016; Staal et al, 2018; Strock et al, 2019) and Nelson tends to be lower (Balci et al, 2021; Flack et al, 2016). Different to us, prior comparisons using DXA-derived RMR showed close predictions (Koehler et al, 2016; Strock et al, 2019) but these studies were on ovulatory exercising women but did not assess RMR in men.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, comparisons of RMR against predictive RMR formulas represent potential markers of RMR suppression when RMR measured /RMR predicted (RMR ratio ) is under a certain threshold value (Staal et al, 2018; Strock et al, 2019). Prediction equations have utility in clinical settings, as allow estimation of resting energy needs of individuals in normal conditions, but the accuracy of these equations is variable and some equations are more suited to different populations (Balci et al, 2021; Flack et al, 2016; Schofield et al, 2019), which, in turn, can impact RMR ratio . Moreover, the accuracy of metabolic carts to measure RMR can be variable (Cooper et al, 2009; Kennedy et al, 2014), ensuring RMR ratio may also be impacted by the selection of equipment.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Athletes are often considered to be at lower risk for CVD due to their high levels of physical activity and tness. (5,6) Athletes are a unique population that requires special attention when it comes to their health and wellbeing. They engage in intense physical activity, which can have both positive and negative effects on their health.…”
Section: Introductionmentioning
confidence: 99%